Community Views on Non-Formal Education in Pamekasan for Society-Based Education - Oktafiana, Shinta; Imdadur Rohman; Ila Wilayatul Jannah; Dina Arina; Hawaijil Asrori (Universitas Terbuka, 2024)
Non-formal education plays a crucial role in providing learning opportunities to individuals who may not have access to formal schooling. In the context of Pamekasan, a region in Indonesia characterized by its diverse culture and socio-economic background, non-formal education serves as a vital tool for addressing educational gaps and empowering marginalized communities. This research aims to explore the perspectives and experiences of the local community in Pamekasan regarding non-formal education initiatives. By understanding the community views, we can identify the strengths, challenges, and potential improvements needed in non-formal education programs. This research uses a descriptive quantitative method with random survey data collection techniques to 60 respondents consisting of productive age adolescents and parents. This study seeks to contribute valuable insights that can inform policymakers, educators, and stakeholders in enhancing the effectiveness and relevance of non-formal education in Pamekasan. Through this exploration, we aim to shed light on the importance of community engagement and participation in shaping educational policies and practices. The results of this study are community perceptions of non-formal education, the role of non-formal education, and the benefits of non-formal education.